Correlation Between Health Status And Comfort In HIV/AIDS Patients Referred To Imam Khomeini hospital In 1391 - Safavi Bayat, zahra; Ashketorab, tahere (Advances in Nursing & Midwifery, 2015)
is a very complicated process ,so affects different dimentions of physical health,social,spiritual and psychological aspects of an individual. The aim of this study was determine the correlation between general(overall)comfort with health status in patients with HIV/AIDS was conducted in 1391. Methods and Material: This descriptive – correlation study was performed on 25 HIV/AIDS patient that refferd to Imam Khomeine Hospital in Tehran in 1391 by convenience sampling methods. A questionnaire with items related to demographic information,36-Item-Form Health Survey(SF-36) and general comfort questionnaire was used for data collection. Its validity was assured by content validity method. Data were analyzed using SPSS 16 software . A Pearson correlation coefficient was calculated to determine the relationship between variables. Findings: Based on the finding average of ages was 36. 44±10. 43 who 60% were married and 64% were lived with their partner and children. The mean of physical status and psychological ,social- economic status, total health status and general comfort was 41. 68±13. 56,36. 84±17. 38,31±14. 61,109±34. 86,86. 48±22. 63. The relationship between stage of disease and physical health status and married and total health status, and Physical health and psychological health status(p=0. 001,r = 0. 9)was significant(P= 0. 02, r = 0. 4),(P= 0. 001, r=0. 6). Conclusion: According to the results, some features of AIDS can associated with different dimentions health status which eventually may be affect general comfort in HIV/AIDS patients. Keywords: Health status, General Comfort, Comfort, HIV/AIDS.